Tailoring the future of MSME marketing: A study on leveraging customer data for personalized experiences - Suryawijaya, Tito Wira Eka; Wardhani, Masitha Fahmi (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
MSMEs play an important role in the global economy, employing nearly 90% of the workforce and contributing nearly 50% of the world's gross domestic product. However, many MSMEs have difficulty finding and retaining repeat customers, which is one of the main challenges for small businesses. This study aims to find out how customer data can be used to improve marketing strategies and meet customer needs and preferences more effectively. This research also aims to provide solutions and recommendations for MSMEs to improve their marketing through personalizing the experience for their customers. This study uses the SEM-PLS method with a quantitative approach. The population is taken from SMEs operating in the city of Semarang. 100 Samples are determined through Quota Sampling. Personalized marketing involves using customer data to customize the customer experience, which can create a closer relationship between customers and MSMEs. This research is still limited to the effectiveness of Personalized Marketing on customer loyalty in MSMEs. There have been many studies that discuss MSME customer loyalty with the marketing communication method. However, there are not many studies that specifically discuss personalized marketing for MSMEs.